Evaluation of Rifalazil in a Combination Treatment Regimen as an Alternative to Isoniazid-Rifampin Therapy in a Mouse Tuberculosis Model - Lenaerts, Anne M. (American Society for Microbiology, 2000)
The newer rifamycin, rifalazil (RLZ) (previously known as KRM-1648), has been shown in prior experiments to be a highly potent drug against Mycobacterium tuberculosis. In this report, we studied the efficacy of RLZ in combination with pyrazinamide (PZA) and ethambutol (EMB) in a long-term in vivo experiment and compared their activity with the isoniazid (INH)-rifampin (RIF) combination which is presently used in the clinic. Combinations of RLZ with PZA alone or with both PZA and EMB were both found to have sterilizing activities comparable to that of the INH-RIF combination but significantly better activity with respect to relapse of infection. These results suggest that RLZ, or other agents with similar activity, could be combined with available agents to act as a potential alternative drug regimen to the currently used INH-RIF combination.